2011
DOI: 10.1186/1756-3305-4-242
|View full text |Cite
|
Sign up to set email alerts
|

The burden of moderate-to-heavy soil-transmitted helminth infections among rural malaysian aborigines: an urgent need for an integrated control programme

Abstract: BackgroundSoil-transmitted helminth (STH) infections, among the most common neglected tropical diseases, continue to be a major threat to the health and socioeconomic wellbeing of infected people especially children in developing countries.MethodsA cross-sectional study among 254 aboriginal schoolchildren was conducted in order to determine the current prevalence and intensity of infections and to investigate the potential risk factors associated with moderate-to-heavy burden of STH infections among these chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
53
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 22 publications
14
53
1
Order By: Relevance
“…These findings were consistent with other local studies conducted among the Orang Asli communities where T. trichiura infection had the highest prevalence (range: 26% to 98.2%), followed by A. lumbricoides infection (range: 19% to 67.8%) and hookworm infection (range: 3% to 37%). [5][6][7][8][9] Hence, the findings in this study not only show that the prevalence of STH remains high but the distribution pattern of STH also remains unchanged among the Orang †Variables were confirmed by multiple logistic regression analysis as significant predictors of STH.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…These findings were consistent with other local studies conducted among the Orang Asli communities where T. trichiura infection had the highest prevalence (range: 26% to 98.2%), followed by A. lumbricoides infection (range: 19% to 67.8%) and hookworm infection (range: 3% to 37%). [5][6][7][8][9] Hence, the findings in this study not only show that the prevalence of STH remains high but the distribution pattern of STH also remains unchanged among the Orang †Variables were confirmed by multiple logistic regression analysis as significant predictors of STH.…”
Section: Discussionmentioning
confidence: 50%
“…Likewise, several studies conducted in recent years reported a high prevalence of STH infections, which ranges from 90% and up to 100% among Orang Asli communities. [5][6][7][8][9] Of the three STH species, T. trichiura infection was the most predominant, followed by A. lumbricoides infection and hookworm infection. These findings were consistent with other local studies conducted among the Orang Asli communities where T. trichiura infection had the highest prevalence (range: 26% to 98.2%), followed by A. lumbricoides infection (range: 19% to 67.8%) and hookworm infection (range: 3% to 37%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations